Coagulation Profile In Diabetes Mellitus And Its Association with Microvascular Complications in Uncontrolled and Controlled Diabetes at Edo Specialist Hospital, Benin-City, South-South, Nigeria - fidelis oyakhire; Babatunde Ishola Gabriel Adejumo; Olufunke Victoria Aiyegbusi; Enehizena Osaro Ogie; Eseoghene Valentine Egho; Promise Bassey Ochannah; Enor Sylvia; Usman Itakure Abdulkadir (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Diabetes mellitus induces coagulopathies by glycating haemoglobin, prothrombin, fibrinogen, and other proteins involved in the clotting mechanism. Shortened PTTK and PT represent a hypercoagulable state related to an elevated thrombotic risk and a negative cardiovascular effect, both of which can lead to the onset and progression of microvascular and macrovascular problems. The study aims to compare the coagulation profile in diabetes-related microvascular complications in clients with uncontrolled and controlled diabetes at an Edo specialty hospital in Benin City. A hospital-based case-control study was carried out at ESH in Benin City. Two hundred eighty individuals were recruited for the study, including 215 diabetes patients (55 type I diabetes, 160 type II diabetes, and 65 non-diabetics) attending the outpatient department of ESH in Benin City. Blood was drawn for coagulation and biochemical assays. Diabetes patients had significantly lower levels of PT and PTTK compared to non-diabetes controls (p<0.05). Fibrinogen and D-dimer levels were considerably higher (p<0.05). The PTTK level was much lower in type 2 diabetes than in type 1 diabetes, and there was a significant difference in platelet count between type 1 and type 2 diabetes. Female diabetes patients had lower levels of PTTK and PT than male diabetic patients. Furthermore, in diabetes with complications, the levels of PTTK and platelet count were lower (p0.05). It was discovered that insulin treatment decreased platelet count, whereas sulfonylurea increased fibrinogen levels in people with diabetes. Diabetes may increase the risk of clotting, as indicated by shorter PTTK, PT, and higher fibrinogen and D-dimer levels compared to controls. The coagulation profile should be evaluated as a regular screening test in diabetes patients to reduce the incidence and prevalence of vascular burden and to improve quality of life.